The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1002/ange.202210365
|View full text |Cite
|
Sign up to set email alerts
|

Operando Quantified Lithium Plating Determination Enabled by Dynamic Capacitance Measurement in Working Li‐Ion Batteries

Abstract: The access to full performance of state-of-the-art Li-ion batteries (LIBs) is hindered by the mysterious lithium plating behavior. A rapid quantified lithium plating determination method compatible with actual working conditions is an urgent necessity for safe working LIBs. In this contribution, the relationship between electrical double layer (EDL) capacitance and electrochemical active surface area (ECSA) of graphite anodes during the Li-ion intercalation and Li plating processes is unveiled. We propose an o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
(16 reference statements)
0
3
0
Order By: Relevance
“…In addition, the EIS results of batteries with Li plating also show different characteristics. ,, Figure a exhibits the Nyquist plot of a fully discharged LIB impedance and the corresponding equivalent circuits. The point intersecting the real axis at the high frequency is the ohmic resistance ( R Ω ), the two semicircles in the high- and medium-frequency regions show the SEI impedance ( R SEI ) and charge transfer impedance ( R ct ), respectively, and the diagonal line in the low-frequency region represents the solid phase diffusion process of Li + Figure b–d depicts the initial and final EIS results of the LIBs at different temperatures and C rates.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the EIS results of batteries with Li plating also show different characteristics. ,, Figure a exhibits the Nyquist plot of a fully discharged LIB impedance and the corresponding equivalent circuits. The point intersecting the real axis at the high frequency is the ohmic resistance ( R Ω ), the two semicircles in the high- and medium-frequency regions show the SEI impedance ( R SEI ) and charge transfer impedance ( R ct ), respectively, and the diagonal line in the low-frequency region represents the solid phase diffusion process of Li + Figure b–d depicts the initial and final EIS results of the LIBs at different temperatures and C rates.…”
Section: Resultsmentioning
confidence: 99%
“…To address the issue of Li plating in LIBs, it is necessary to have a deep understanding of the Li plating pattern, which makes the relevant study particularly important. The effects of C rate and low temperature on the Li plating pattern have been studied by vast works. It has been shown that large C rates accelerate the onset of Li plating, while low temperature causes the graphite to plate Li for reaching 0 V vs Li/Li + earlier during charging. The reversibility of Li plating has also been investigated, and better reversibility of Li plating has been found at lower C rate cycling. In addition, the variation patterns of Li plating, such as the growth process of Li plating and the impedance change of the batteries before and after Li plating, have been studied to improve the understanding of Li plating. The growth of whisker-like Li, dendritic Li, mossy Li, and bulk Li has been revealed extensively, and the impedance change pattern has been proposed to predict the onset of Li plating. , Previous studies have made substantial contributions to Li plating cognition, confirming that Li plating is highly sensitive to low temperatures and C rates. , However, a detailed summary of Li plating patterns under the combined effect of low temperature and C rate is lacking, and quantitative analysis is still insufficient.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation